A look inside cardiopulmonary resuscitation: A 4D computed tomography model of simulated closed chest compression. A proof of concept. (August 2020) - Hansen, Kasper; Machin, Ruth; James, Jonathon; Coats, Timothy; Rutty, Guy N.
Highlights: We present a method to create time-resolved volumetric (4D) CT models simulating CPR thoracic and abdominal organ movement. This novel method generates 4D models from incremental closed chest compressions. The method could yield new information related to CPR chest compressions. It could assist with the testing and development of new resuscitation protocols and interventions. The visualisation of thoracic and abdominal content movement during chest compressions could assist teaching CPR. Abstract: Aim: To mimic chest compression during cardiopulmonary resuscitation (CPR), this study aimed to produce time-resolved 3D (volumetric) reformats of thoracic and upper abdominal tissue movement during incremental closed chest compression/decompression from 0 to 8 to 0 cm. Methods: Sequential angiography enhanced computed tomography (CT) scans were acquired from a recently deceased, consented adult cadaver with 1 cm incremental closed chest compression/decompression. Three compression/decompression sequences from 0 to 3 cm, 0 to 5 cm, and 0 to 8 cm, respectively, were scanned using a radio-opaque, manually operated, chest compression device. The multiphase volumetric data sets were compiled into 4D models that allowed for multiplanar reformatted and volume rendered image manipulation. Results: Time-resolved volumetric (4D) models were produced using freeware to post-process the static CT scans. The 4D models allowed the study of simulated thoracic and upper abdominal content movement during closed chest compression. Conclusions: The method described could assist CPR researchers and educators in the development and demonstration of effective CPR protocols.